2014
DOI: 10.1007/978-3-319-14139-8_25
|View full text |Cite
|
Sign up to set email alerts
|

Former Students’ Views on the Usefulness of Conceptual Modeling Education

Abstract: Abstract. A big challenge for education and research in Requirements Engineering and Conceptual Modeling (RE/CM) is the need for much more empirical research about the use in practice of RE/CM, including the practical impact of CM education. Former students of RE/CM are potential prescriptors of the RE/CM concepts, methodologies and tools that they have learnt, but they are also conditioned by the current use of those same issues in practice. In this paper we focus on the views that former students of a RE/CM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Perhaps this is because student evaluations, assignment sheets, and exams are the typical means of assessment of student performance; however, another way of assessing learning outcomes is to measure student performance against industry needs, such as through a graduate alumni surveys of preparedness. This was done in [184], where researchers found that perceived usefulness of instructed documentation In summary, we consider it a positive development that educational approaches have taken a keen focus on improving students' industry-readiness and are moving away from rote memorization in favor of formative learning. However, many of these approaches aim at doing so without consideration of industry needs.…”
Section: Authenticity and Industry-readinessmentioning
confidence: 92%
See 2 more Smart Citations
“…Perhaps this is because student evaluations, assignment sheets, and exams are the typical means of assessment of student performance; however, another way of assessing learning outcomes is to measure student performance against industry needs, such as through a graduate alumni surveys of preparedness. This was done in [184], where researchers found that perceived usefulness of instructed documentation In summary, we consider it a positive development that educational approaches have taken a keen focus on improving students' industry-readiness and are moving away from rote memorization in favor of formative learning. However, many of these approaches aim at doing so without consideration of industry needs.…”
Section: Authenticity and Industry-readinessmentioning
confidence: 92%
“…12). Most of these studies occurred before 2012 (i.e., when Ouhbi et al concluded) with the exception of [17,66,87,117,125,184] and [190]. Ouhbi et al were correct to point out that more instructional focus was required, as these 29 studies made up a mere 19.1% of all our selected studies (compared to 18.4% for "elicitation" alone).…”
Section: Promote Requirements Modeling Validation and Verification An...mentioning
confidence: 95%
See 1 more Smart Citation
“…These CS represent three kinds of systems: (i) the Super Stationery system (SS), which makes use of classes with attributes and derived attributes, associations and constraints but has no generalizations, (ii) an Expense Report management system (ER) that uses fewer classes and relations but more constraints, and lastly, (iii) the Sudoku Game (SG) system [20], which is more variant-rich than the other two CS including generalization relations, derived associations and aggregations. The size of each CSUT is shown in Table 2 in terms of model elements.…”
Section: Conceptual Schemas Under Testmentioning
confidence: 99%